PENGARUH PROMOSI DAN KEMASAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK CHITATO YANG DIMEDIASI OLEH BRAND AWARENESS - Setiawati, Mega; Lumbantobing, Rudolf (Manajemen Bisnis Kompetensi, 2017)
ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ  AbstractÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ  This study is focused in exploring the influence of promotion and packages ÃÂ toward consumerÃ¢â¬â¢s purchasing decision on chitato product, which mediated by brand awareness. Selection of the sample in this study is conducted by using judgemental sampling, so that the sample was selected amount of 105 respondents. The data collection is done by direct observation through questionaire instrument. The data are analyzed by using path analysis. The results showed that packaging and promotion have significantly positive effect on brand awareness. And brand awareness has significantly positive effect on chitato product purchasing decisions. Promotion has a significant positive effect on brand awareness, but promotion is not significantly positive effect on chitato product purchasing decisions. Brand awareness mediates positive influence of promotion and packaging toward the chitato product purchasing decisions. Thus the positive effect of promotional and packaging on chitato purchasing decisions will be more positive when the brand awareness in the minds of customers is increasing.Keywords: promotion, package, brand awareness, purchasing decision, path analysis.